'Mother's Blood, Father's Land': Native Title and Comparative Land Tenure Modelling for Claims in 'Settled' Australia. Issue 1 (March 2017) - Morton, John
Abstract : Anthropologists working in the field of Australian native title are required to piece together the early laws and customs of claimant groups and assess the degree to which these have continued since the assumption of British sovereignty. The former task is often difficult in south‐eastern Australia because of a lack of good quality early records. I suggest here that there are general principles of Aboriginal land tenure that can be recovered from elsewhere in Aboriginal Australia, where the ethnography is of a better standard, and these can be used as a guide for working with the patchier materials characteristic of the south‐east. The principles mainly cohere around the organic relationship between patrilineal descent and complementary filiation, and are shown to be relevant to the modelling of contemporary south‐eastern tenure, where people speak of 'bloodlines' identified with ancestral lands.